Efektivitas Program Pembelajaran Taman Pendidikan Al-Qur’an (TPA) dalam Meningkatkan Kemampuan Membaca Al-Qur’an - Abdurrohman, Dede; Anwar, Syaiful; Istahana, Istihana; Istanjir, Akhmad (An-Nuha, 2023)
TPA as an educational institution should be an effective means for creating critical and creative understanding and become a place for students to develop and direct their potential so that they can become an independent generation. TPA Al-Hikmah, Sidosari Natar Village, South Lampung, in its learning activities, applies the Iqra' teaching method, where this method is considered to have a good acceleration system in mastering the ability to read the Al-Qur'an. However, the problem faced by TPA Al Hikmah is that there is only 4 teaching staff while the number of students reaches hundreds. This research uses a qualitative descriptive approach with a sampling technique using snowball sampling while the data collection techniques used are observation, interviews, and documentation using self-instruments as the main instrument. The results of this research show that improvements in reading the Al-Qur'an can be seen in the application of the CBSA system and direct methods in the teaching and learning process. However, all of this is only a reference for the ustadz/ustadzah at TPA Al-Hikmah, while the success factor that determines the effectiveness of learning at TPA Al-Hikmah in improving students' ability to read the Al-Qur'an lies in the ability of the ustadz/ustadzah in making the assistance and control system more effective. which is good in the private system while still referring to the application of the module system in teaching iqra' so that students get good results in reading the Al-Qur'an. Apart from that, the ustadz/ustadzah at TPA Al-Hikmah vary their teaching methods using the lecture method, the play while learning method, the insert method in the form of stories about good role models, especially in the classical system.